2021
DOI: 10.1097/lbr.0000000000000815
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curves for Electromagnetic Navigation Bronchoscopy Using CUSUM Analysis

Abstract: Background: Electromagnetic navigation bronchoscopy (ENB) is a relatively new and technically demanding procedure for the guidance of bronchoscopic biopsy to help locate small lung lesions. The results in experienced hands are well described. However, we do not know the results in unexperienced hands-in other words, we have no knowledge about how fast you can learn the procedure.Aim: The aim of this study was to draw learning curves for beginners in ENB using Cumulated Sum (CUSUM) analysis, a method for quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…To support this, a randomized trial found that simulation-based training was more efficient than traditional apprenticeship training in the beginning of novice EBUS operators’ learning curves [ 16 ]. Furthermore, earlier studies evaluating EBUS and ENB have shown that the learning curves of individual trainees vary considerably [ 14 , 17 ] and international guidelines now recommend the use of structured assessment of performance, instead of relying on an arbitrary number of performed procedures to ensure competency [ 18 ]. Furthermore, earlier studies evaluating EBUS and ENB have shown that learning curves of individual trainees vary considerably [ 14 , 17 ] and international guidelines now recommend the use of structured assessment of performance instead of relying on an arbitrary number of performed procedures to ensure competency [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To support this, a randomized trial found that simulation-based training was more efficient than traditional apprenticeship training in the beginning of novice EBUS operators’ learning curves [ 16 ]. Furthermore, earlier studies evaluating EBUS and ENB have shown that the learning curves of individual trainees vary considerably [ 14 , 17 ] and international guidelines now recommend the use of structured assessment of performance, instead of relying on an arbitrary number of performed procedures to ensure competency [ 18 ]. Furthermore, earlier studies evaluating EBUS and ENB have shown that learning curves of individual trainees vary considerably [ 14 , 17 ] and international guidelines now recommend the use of structured assessment of performance instead of relying on an arbitrary number of performed procedures to ensure competency [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, earlier studies evaluating EBUS and ENB have shown that the learning curves of individual trainees vary considerably [ 14 , 17 ] and international guidelines now recommend the use of structured assessment of performance, instead of relying on an arbitrary number of performed procedures to ensure competency [ 18 ]. Furthermore, earlier studies evaluating EBUS and ENB have shown that learning curves of individual trainees vary considerably [ 14 , 17 ] and international guidelines now recommend the use of structured assessment of performance instead of relying on an arbitrary number of performed procedures to ensure competency [ 18 ]. It is also important to note that other factors also contribute to the complexity of the ENB procedure, with one major important problem being the challenge of image-to-patient divergence due to (1) the patient usually not being positioned in the exact same position during CT-imaging and on the operation table and (2) the lungs, especially the lower parts, potentially moving during breathing, and thereby, the real-time location of a given target will often not perfectly match the position known from the preoperative CT-scan [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Journal of Bronchology & Interventional Pulmonology , Toennesen et al4 used CUSUM to calculate the learning curves for 4 experienced bronchoscopists, albeit novice operators in ENB from 3 different hospitals in Denmark. The outcome of each ENB was categorized as either success or failure based on sample adequacy defined as malignant cells at cytopathologic evaluation or nonmalignant diagnosis at cytopathologic and/or microbiological evaluation with verification of the diagnosis at follow-up after at least 6 months.…”
mentioning
confidence: 99%
“…Different approaches can lead to different conclusions about the typical number of procedures needed to achieve competence. For example, Lee and colleagues found 15 ENB procedures were required for all fellows to achieve a competency standard based on checklist scores, whereas Toennesen and colleagues found an average of 40–50 ENB procedures were required for experienced bronchoscopists to achieve a competency standard based on diagnostic accuracy ( 12 ). The difference between the learning curves in these studies can be explained by differences in how performance was assessed (checklist vs. clinical outcome).…”
mentioning
confidence: 99%